FOMO, Kesadaran Merek, dan Minat Membeli Konsumen: Bukti dari Pasar Parfum Niche di Indonesia - Eko Yuliawan; Mark Anthony Cabia (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the effect of Fear of Missing Out (FOMO) on purchase intention, mediated by brand awareness among consumers of niche or premium perfumes. The research employs a quantitative approach with an explanatory design. Data were collected online via Google Forms during the period of April to June 2025, involving 134 respondents who had previously purchased niche perfumes. The sampling technique used was purposive sampling, with criteria focusing on consumers who have experience purchasing premium perfumes. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM–PLS) method. The results show that FOMO has a positive effect on purchase intention, both directly and indirectly through brand awareness. These findings indicate that brand awareness plays a crucial role in strengthening the psychological and social influence on consumers’ purchase intentions. Theoretically, this study broadens the understanding of consumer behavior in the context of exclusive products, while practically, it provides insights for marketers to leverage FOMO-based strategies to enhance brand awareness and stimulate purchase intention. The originality of this study lies in integrating emotional and social factors to explain purchasing behavior in the niche perfume market in Indonesia.